International Students in Transition: Voices of Chinese Doctoral Students in a U.S. Research University - Zhang, Yi (Leaf) (Journal of International Students, 2016)
In this study, I focused on international Chinese doctoral students and sought to better understand their lived experience in transition to U.S. higher education. I also aimed to explore strategies that can be employed to improve these students’ academic and sociocultural experiences on American campuses. Guided by the adult transition theory (Goodman, Schlossberg & Anderson, 2006), this study used an interpretive phenomenological method. Qualitative data were collected from in-depth focus group interviews. The findings of this study informed higher education educators and practitioners about unique challenges faced by international Chinese graduates in transition and provided insightful knowledge for new practice, programs, and policies that can be created to improve international students’ transition and success